THE RELATION OF LONG-SUFFERING FOR HYPERTENSION AND FRAILTY WITH COGNITIVE FUNCTION STATUS IN ELDERLY AT PSTW BUDI MULIA 2 CENGKARENG - Ahmad, Shieva Nur Azizah; Hastuti, Hera; Oktavia, Nanda Rizki; Winahyu, Karina Megasari (Universitas Respati Yogyakarta, 2021)
The increase in the elderly population in the world has resulted in an epidemiological transition in the health sector so that there can an increase in the number of morbidity due to degenerative diseases, namely cognitive function problems. Poor cognitive function status can influenced by one of the respondent's characteristic domains such as the length of history of hypertension and the domain of health risk factors such as frailty. This study aims to find the relationship between long-suffering from hypertension and frailty on cognitive function status in elderly patients at PSTW Budi Mulia 2 Cengkareng. The research design used is descriptive analytic with a cross-sectional approach. Collecting data using the questionnaire The Edmonton Frailty Scale (EFS) and the Short Portable Mental Status Questionnaire (SPMSQ) which have been test for validity and reliability. The sample consisted of 58 respondents who were take using purposive sampling technique. Data analysis used in this study is the Pearson correlation. This study shows that 81% of respondents are between 60-74 years old, female gender is 67.2%, primary school education level is 56.9%. Meanwhile, the length of the elderly suffering from hypertension â‰¤5 years was 65.5%, mild frailty was 67.2%, and moderate cognitive dysfunction was 36.2%. The results of the Pearson correlation statistical test showed that there was a relationship between the length of suffering from hypertension and the cognitive function status with a value of p = 0.004 and there was a relationship between frailty and the cognitive function status with a value of p = 0.001. Elderly advised to support health by controlling a low salt diet so that cognitive decline does not become chronic so that they do not develop dementia and control frailty by eating foods high in energy and protein so that they do not worsen cognitive function. Keywords: Frailty; Length of Suffering from Hypertension; Status of Cognitive Function